HUBUNGAN BEBAN KERJA FISIK DAN KUALITAS TIDUR TERHADAP KELELAHAN KERJA PADA PEKERJA WANITA DENGAN PERAN GANDA DI PT ISKANDARTEX SURAKARTA - Az Zahra, Cellina Salsabila Shofa; Sumardiyono, Sumardiyono; Sari, Yulia (Jurnal Kesehatan Masyarakat, 2024)
Dual-role women workers in the industrial sector will endure extra burdens and require greater energy. Dual-role women workers tend to experience work fatigue because they have a bigger workload. The extra workload and the imbalanced sleeping need can cause health problem such as work fatigue. The research aims to determine the correlation between physical workload and sleep quality with work fatigue of dual-role women workers at PT Iskandartex Surakarta. This research used an analytic observational study, with a cross-sectional approach. Respondents from this study were all women workers of reaching unit PT Iskandartex Surakarta totaling 30 people with a sampling technique using total sampling. Measurement data used a weight scale and stopwatch to measure physical workload, sleep quality measurement used the pittsburgh sleep quality index, and a reaction timer used to measure work fatigue. The data analysis technique used chi-square for bivariate test and binary logistic regression for the multivariate test. The outcomes showed the majority of respondents had medium physical workload (53,5%), poor sleep quality (56,7%), and experienced work fatigue (60%). The chi-square test results showed that there was a significant relationship between physical workload and work fatigue (p value = 0,000) and there was also a significant relationship between sleep quality and work fatigue (p value = 0,000). The result of the binary logistic regression test showed that the physical workload (OR = 38,022) is more influenced by fatigue than sleep quality (OR = 16,190).